Jamaah Ahmadiyah: Ideologi dan Pola Keberagamaan di Tengah Kemajemukan - Rahmatullah, Lutfi; Istianah, Istianah (DINIKA : Academic Journal of Islamic Studies, 2020)
This study aims to explore the religious patterns of the Jemaat Ahmadiyya in Indonesia, with a focus of the study in the villages of Gondrong, Banten and Manislor, Kuningan, West Java, especially about the views related to religious and state relations, and their existence as a ‘minority group’ in Indonesia. Based on a phenomenological approach, wherein the data is obtained by involving the researcher directly in the social process of the study subject, the results of this study show that the relationship between religion and state is understood by Ahmadiya in the framework of the concept of Khilafah; a concept that is believed to be inevitable, as a form of continuous moral guidance from the prophetic system. But in term of operationalization is not oriented towards political practice and does not clash with state ideology. Khilafah is understood only in the context of religion, spirituality, and other religious rites. As a minority group living in pluralistic community culture, the Ahmadiyya sees that the various cases of violence that have befallen their followers are a form of manifestation of the maturity level of the Indonesian people in responding to differences. So, the diversity that exists is still a trigger for potential conflict.